Practical Considerations for Implementing Virtual Care in Physical Medicine and Rehabilitation: For the Pandemic and Beyond. (June 2020) - McIntyre, McKyla; Robinson, Lawrence R.; Mayo, Amanda
Abstract : Abstract: This article outlines a practical approach to quickly implementing virtual care for physiatrists. This skill is relevant not only during times of a pandemic, when face to face care is impossible, but is also valuable when caring for patients who have physical, financial, logistic, or other challenges to on-site care. Key themes covered in this article include selecting appropriate virtual care platforms, consenting patients for virtual care and conducting successful virtual visits. It also reviews strategies for performing virtual physical examinations and engaging learners in virtual care.